Calculation of the initial DNA damage induced by alpha particles in comparison with protons and electrons using Geant4-DNA. (2nd June 2020) - Moeini, Hossein; Mokari, Mojtaba; Alamatsaz, Mohammad Hassan; Taleei, Reza
Abstract: Purpose: Interaction of ionizing radiations with cells leads to single- and double-strand breaks (SSBs and DSBs) as well as base lesions of DNA. Employing the Geant4-DNA toolkit, we simulated the transportation of primary alphas and secondary particles in liquid water to study the damage in the form of SSBs and DSBs. Materials and Methods: Simulations were performed in a spherical water medium, where we used a B-DNA model and classified the DNA damage and its complexity. We assumed that in a certain vicinity of the DNA volume, energy depositions of more than 17.5 eV or hydroxyl radicals with a chemical-reaction probability of 0.13 would lead to strand breaks. Results: The results of 2 to 20 MeV alpha particles showed that more than 65% of the energy-deposition cases within the DNA volume would result in a form of break. The frequency pattern of higher-complexity damage types appeared to peak at higher deposited energies. Conclusion: We observed a reasonable agreement in terms of trend and value between our DSB yield results and experimental data. The yield results, as function of LET, suggested independence from particle type and converge to some extent at large LET. This manifests the dominant contribution of secondary electrons.